Administrative Mechanism in Management Techniques in Intensive Shrimp Farming (Litopenaeus Vannamei) in West Java - Muslimin, Muslimin; A, M. Awaluddin; Yunus, Andi Muhammad; Asdar, Muhammad; Triadi, Feby (Pinisi Business Administration Review, 2025)
Artificial feed is the main input of energy sources provided so that shrimp growth becomes optimal. Appropriate feeding can spur the growth and development of vaname shrimp optimally so that productivity can be increased and get low FCR. This Final Practical Work (KPA) will be carried out from January 15, 2024 to March 31, 2024 at West Java Tasikmalaya, West Java, with the aim of knowing feed management in vanname shrimp rearing in intensive ponds, calculating survival rates, ABW, ADG, FCR and calculating business analysis on vanname shrimp rearing in intensive ponds. The data analysis techniques used in the preparation of this report are descriptive and quantitative analysis. Feed management in vaname shrimp starts from feed handling, type and form of feed, nutritional content of feed, feed program, feeding and anco control. Stocking density of 150 heads/m2 with a maintenance period of 120 days using Haida brand feed. For the feed program using two methods, namely blind feeding and feeding rate. During maintenance, biomass was obtained 1.1 09 kg, ABW 4.35, ADG 0.16 gr, SR 85 %, and FCR 1.7. The results of the business analysis calculation show that shrimp farming activities in Feed Management Techniques on Intensive Enlargement of Vaname Shrimp (Litopenaeus vannamei) at West Java is a worthy effort because it obtains a profit value of Rp. 2,244,866,177 from BEP production of 51,864 kg and BEP at a price of Rp. 42,542 and Pay Back Period (PP) obtained 3. period to return capital.